Hospital admission for mental illness: Comparing women who gave birth in a private hospital and a public hospital. (12th November 2020) - Sims, Deborah; Xu, Fenglian; Fowler, Cathrine; Catling, Christine
Abstract : Background: In Australia, perinatal care is provided through a mix of government and private funding. Women who give birth in a private hospital are less likely to receive depression screening and psychosocial assessment and are less likely to access parenting services that support mental health outcomes, compared to women who give birth in a public hospital. Aim: The aim of this study was to determine the risk of one outcome of perinatal mental illness – hospital admission – for women who gave birth in private hospitals compared to women who gave birth in public hospitals. Methods: This population‐based cohort study employed binary regression analysis of state government data. Linkage of the Perinatal Data Collection, Registry of Births, Deaths and Marriages, and Admitted Patients Data Collection (2003–2009) has provided comparative information on women admitted to any hospital during the first year after birth with a primary diagnosis of mental illness. Results: In the first year after birth, women who gave birth in private hospitals were more likely to be admitted to a hospital with a primary diagnosis of mental illness (rate = 2.54%, 95% CI = 2.40–2.68%) than women who gave birth in public hospitals (rate = 1.68%, 95% CI = 1.61–1.75%). Conclusion: The increased likelihood of admission for postnatal mental illness may indicate increased risk of developing a mental illness for women who gave birth in a private hospital.